Resource and Hazard Analysis of Selected Farmland Communities Along Bicol River - Jessica Dionne R. Nunag; Ricky P. Laureta; Kier P.Gasga; Diomerl Edward B. Baldo; Maria Petra O. Ebron (International Review of Social Sciences Research, 2023)
This study provides information on resource and hazard maps in selected farmland communities along Bicol River Basin. It specifically identifies and maps-out the agri-fishery resources, climate-related hazard areas, agricultural infrastructures, landmarks and other relevant resources and determines the climate adaptation practices and strategies of agriculture and livestock in the community. Resource and hazard mapping was used as a tool in the Participatory Rural Appraisal (PRA). Six communities from representative project beneficiaries from the Department of Agriculture Project Funded namely Baao (Sta. Eulalia and San Fransisco), Canaman (Mangayawan and San Fransisco) and Minalabac (Taban and Del Carmen-Del Rosario) were the participants. Results of PRA revealed that the majority of land resources in the barangays are being utilized in rice, high-value crop and corn farming while fishing, livestock, and poultry are considered other livelihood sources. Their geographic location and advantage is also its weakness in agriculture as a significant part of its farmland is prone to flooding during the wet season and drought during the dry season. Both sites in Canaman also experience saline intrusion. Most farmers practice adaptation strategies like using early maturing, submergence tolerant and saline-tolerant, and seeking another potential source of livelihood. The resource and hazard map not just depicts various aspects related to agriculture; it is also a useful tool to enhance resilience from natural hazards and disasters.